Combined Pericardium P6 Acupressure & Peppermint Aromatherapy on Nausea in First-Trimester Pregnancy - Handajani, Sih Rini; Azzahra, Luthfiya Humairah; Sari, Lutfiana Puspita (Politeknik Kesehatan Kementrian Kesehatan Gorontalo, 2025)
According to WHO, hyperemesis gravidarum affects 12.5% of pregnancies worldwide, with Indonesia reporting a 14.8% incidence. Nausea and vomiting occur in 50-70% of first-trimester pregnancies, caused by hormonal changes, particularly HCG, estrogen, and progesterone. Management includes pharmacological and non-pharmacological methods, such as acupressure at the pericardium point (P6) and peppermint aromatherapy. Acupressure increases cortisol and metabolism, while peppermint's menthol and methone help reduce nausea.This study aimed to analyze the effect of combining acupressure (P6) and peppermint aromatherapy on nausea intensity in first-trimester pregnant women at the Wedi Klaten Health Center. Using a Quasi-Experimental One Group Time Series Design, 32 respondents received acupressure (7 minutes) and peppermint aromatherapy (3 drops for 15 minutes) every morning for 4 days. Data were collected using the PUQE-24 questionnaire and analyzed with a Paired T-test.Results showed a decrease in nausea intensity from 7.00 to 5.69 on average. Statistical analysis confirmed a significant effect (p = 0.000, p < 0.05). The combination of acupressure and peppermint aromatherapy effectively reduced nausea and vomiting in first-trimester pregnant women. Keywords: Pericardium point (P6) acupressure, peppermint aromatherapy, nausea and vomiting, pregnant women.